2011
DOI: 10.1037/a0022489
|View full text |Cite
|
Sign up to set email alerts
|

A randomized controlled trial of cognitive-behavioral therapy for generalized anxiety disorder with integrated techniques from emotion-focused and interpersonal therapies.

Abstract: Objective-Recent models suggest that generalized anxiety disorder (GAD) symptoms may be maintained by emotional processing avoidance and interpersonal problems.Method-This is the first randomized controlled trial to test directly whether cognitivebehavioral therapy (CBT) could be augmented with the addition of a module targeting interpersonal problems and emotional processing. Eighty-three primarily White participants (mean age = 37) with a principle diagnosis of GAD were recruited from the community. Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
3
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 59 publications
4
125
3
1
Order By: Relevance
“…Participant characteristics are presented in Table 3 and are similar to other GAD samples (e.g., Newman et al, 2011). Men and women did not differ in their STAI, HARS, or BDI-II scores.…”
Section: Resultsmentioning
confidence: 74%
“…Participant characteristics are presented in Table 3 and are similar to other GAD samples (e.g., Newman et al, 2011). Men and women did not differ in their STAI, HARS, or BDI-II scores.…”
Section: Resultsmentioning
confidence: 74%
“…Randomized clinical trials have demonstrated that pharmacotherapy and psychotherapy interventions for MDD reduce anxiety symptoms and such interventions for GAD reduce depressive symptoms (Gorman, 2002;Leichsenring et al, 2009;Newman et al, 2011;Rivas-Vazquez, 2001). However, little is known about the temporal relationship between symptoms of MDD and GAD along the course of treatment and it remains unclear how targeting one disorder results in change in symptoms of the other.…”
Section: Introductionmentioning
confidence: 99%
“…Emotion concept has been getting more importance in evidence-based psychotherapy in recent years (1)(2)(3). Especially in cognitive-behavioral psychotherapy process, it is being thought that schemas and attitudes towards emotions may cause resistance to change of client (4).…”
Section: Introductionmentioning
confidence: 99%